2018
DOI: 10.1162/jocn_a_01195
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsal Attention Network Reflects Both Encoding Load and Top–down Control during Working Memory

Abstract: Abstract■ The dorsal attention network is consistently involved in verbal and visual working memory ( WM) tasks and has been associated with task-related, top-down control of attention. At the same time, WM capacity has been shown to depend on the amount of information that can be encoded in the focus of attention independently of top-down strategic control. We examined the role of the dorsal attention network in encoding load and top-down memory control during WM by manipulating encoding load and memory contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 64 publications
3
52
0
1
Order By: Relevance
“…Interestingly, structures found active in the frontoparietal (FP) region in our study suggest that our task also heavily relies on brain structures involved in spatial attention and working memory (WM; Cona and Scarpazza, 2019 ). In line with their results, we also found a FP pattern of activation, looking very much like the one they observe in their study, that is, an activation pattern resembling the dorsal attention network (DAN; Majerus et al, 2018 ). This FP circuitry is composed of the frontal eye field, superior parietal lobule, and intraparietal sulcus, and it is usually recruited for perceptive visuospatial tasks, but also for spatial operations made on objects mentally visualized.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, structures found active in the frontoparietal (FP) region in our study suggest that our task also heavily relies on brain structures involved in spatial attention and working memory (WM; Cona and Scarpazza, 2019 ). In line with their results, we also found a FP pattern of activation, looking very much like the one they observe in their study, that is, an activation pattern resembling the dorsal attention network (DAN; Majerus et al, 2018 ). This FP circuitry is composed of the frontal eye field, superior parietal lobule, and intraparietal sulcus, and it is usually recruited for perceptive visuospatial tasks, but also for spatial operations made on objects mentally visualized.…”
Section: Discussionsupporting
confidence: 92%
“…This FP circuitry is composed of the frontal eye field, superior parietal lobule, and intraparietal sulcus, and it is usually recruited for perceptive visuospatial tasks, but also for spatial operations made on objects mentally visualized. More generally, the DAN is associated with the internal maintenance of task-related representations (for a review, see Majerus et al, 2018 ), which obviously means spatial representations for spatial tasks. Given their results, and as part of their conclusions, Cona and Scarpazza ( 2019 ) suggest that the DAN is likely to play a key role for working memory, episodic retrieval, and mental imagery.…”
Section: Discussionmentioning
confidence: 99%
“…However, even if neural data suggested that children may progressively use more specific strategies for maintaining serial‐order information in WM, our behavioral data indicated that item and order WM performance increase similarly with age. Therefore, the precise nature of these serial order coding strategies, just like the nature of serial order coding more generally, remains an open question and many different hypotheses having been proposed so far (see Majerus et al, for a discussion).…”
Section: Discussionmentioning
confidence: 99%
“…The left frontoparietal network has been proposed to support attentional control during WM tasks as it overlaps with the dorsal attention pathway. It is observed both in verbal and visuospatial WM tasks, and it is sensitive to WM load in both modalities (Majerus, Péters, Bouffier, Cowan, & Phillips, ; Todd & Marois, ). The right IPS involvement in serial order WM tasks has been associated with temporal and spatial serial order coding processes (Majerus et al, ; Majerus et al, ; van Dijck & Fias, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cortical thickness results offer sMRI evidence for the presence of differential characteristics between BD and HD. The left lateral superior parietal region, which is affected in participants with histories of BD, overlaps with networks that are involved in executive control: such as volitional attention processes ( Majerus, Péters, Bouffier, Cowan, & Phillips, 2017 ) and planning goal directed actions ( Dixon, Girn, & Christoff, 2017 ). This finding builds on prior studies, which reported similar neuromorphometric changes in AUD ( Dager et al, 2015 ; Kim, Im, Lee, & Lee, 2017 ), by showing that these regions are selectively affected in individuals with histories of BD, and might not be generalizable to other types of alcohol misuse.…”
Section: Discussionmentioning
confidence: 99%